Measuring the Unused Capacity for Mature and Immature Area in Palm Oil Nursery Using Time Driven Activity-Based Costing - S. N. A. M., Zaini; Abu, Mohd Yazid (Springer, Singapore, 2021)
The emergence of Malaysia, the world’s leading palm oil producer, has driven the industry to thrive as never before. Recently, there are few issues happen in this plantation which are difficult to observe the establishment of time equation to interpret deviation of activities, the rate establishment do not precisely illustrate the correlation between supplied resources and practical capacity, and the manager do not have a tool to monitor the unused capacity. The aim of this work is to measure the unused capacity for mature and immature area at nursery for a better accuracy. Time-driven activity-based costing (TDABC) is applied as time efficiency can be calculated effectively, idle capacity accurately defined and used and unused capacity individually listed. It also provides more comprehensive understanding of practical resources and its associated costs while measuring processes and encouraging quality improvement. This work considers a data in 2017 to develop the solution. This work found that in pre nursery, the unused capacity of time in mature and immature are −324,174 min and −221,160 min respectively while the unused capacity of allocated cost in mature and immature are RM-145878.30 and RM-75194.40 respectively. Meanwhile, in main nursery, the unused capacity of time in mature and immature are −793 min and 15,385.5 min respectively while the unused capacity of allocated cost in mature and immature are RM-428.22 and RM6154.20 respectively.